Optimization and Evaluation of Bakuchi Oil loaded hydrogel for the Management of Psoriasis (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Novel drug delivery systems offer several advantages as compared to conventional systems. Drugs can be effectively delivered topically by being incorporated into gel, which will prevent first pass metabolism and increase local action for skin conditions. Hydrogels are 3D polymeric system structure of hydrophilic polymers. The main goals of hydrogels are to improve patient compatibility, and release medication at a controlled rate with maximum therapeutic effects. Bakuchi oil is obtained from the seeds of Psoralea corylifolia (family: Leguminosae), which has anti-inflammatory qualities. Research was conducted to investigate how to enhance anti-psoriatic activity by using herbal Bakuchi oil in the form of hydrogel. Carbopol 940 (carbomer) polymer, Transcutol-P as a permeation enhancer, and triethanolamine for pH adjustment were used to prepare hydrogel. The impact of formulation variables, such as concentration of polymer and permeation enhancer, on the formulation responses was assessed. Optimized formulation F8 demonstrated a maximum drug release of 85.36±0.33% in 1 hour. Viscosity and spreadability of formulation F8 were found to be 5089±0.70 cps and 11.45±1.47 gm.cm/sec respectively. The findings suggested that a successful herbal formulation containing Bakuchi oil can be developed with improved rheological properties and good permeation profile.